한국잔디에 발생하는 봄마름병(Rhizoctonia cerealis AG-D)의 가을철 발생보고 - 이정한(Jung Han Lee); 김정호(Jeong Ho Kim); 전창욱(Chang Wook Jeon); 심규열(Gyu Yul Shim); 곽연식(Youn-Sig Kwak) (Weed & turfgrass science, 2019)
2018년 10월 중순 전남 곡성에 소재한 광주골프장에서 봄마름병 병징이 한국잔디에 발생하였다. 일반적으로 봄마름병의 감염시기는 늦은 가을이며 병징은 봄에 나타나지만 본 연구에서 조사한 바에 따르면 가을에 병징이 나타나는 것으로 조사되었다. 초기 병징은 잔디의 잎이 붉은 갈색으로 황화되기 시작하며 엽이와 줄기가 썩고 10월 말경에는30-50 cm의 불규칙한 패취 형태로 병반이 나타났다. 이른 아침 거미줄 모양의 기중균사가 형성되었다. 병원균의 형태학적 특징과 rDNA의 ITS 염기서열을 분석한 결과 Rhizoctonia cerealis AG-D로 동정되었다. 병원균의 최적 생장온도와pH조건은 20℃에서 pH 6으로 각각 나타났다. 가을에 감염된 잔디의 맹아 출현은 건전 잔디에 비하여 현저히 떨어지는것으로 나타났다. 봄마름병의 감염부위는 엽이이고 반면에 라이족토니아마름병은 관부 주위이기 때문에 봄마름병에 감염된 잔디는 라이족토니아마름병에 감염된 잔디보다 잘 뽑히지 않는 특징이 있다. 가을철 발생하는 한국잔디의 봄마름병을 처음으로 보고하고자 한다. In October 2018, symptoms of the spring dead spot (Rhizoctonia cerealis AG-D) disease in Kwang-Ju Country Club at Gokseong, Jeonnam province, South Korea were observed on zoysiagrass (Zoysia japonica Steud.). Spring dead spot symptom commonly appears in spring, however our research showed that the spring dead spot symptom on zoysiagrass could be shown in autumn. The initial disease symptoms were observed on reddish brown leaves and a decaying, irregular-shape patch of the leaf (30-50 cm), developed by the end of October, as the disease progressive. Aerial hyphae, like spider web on the leaves, were observed in the early morning. The causal agent was isolated and identified as Rhizoctonia cerealis AG-D by morphological and molecular characteristics. Optimal temperature and pH for mycelial growth of Rhizoctonia cerealis AG-D were 20℃ and pH 6.0, respectively. Bud formation from the infected tissue in fall season was considerably reduced compared to healthy lawn in spring. The spring dead spot infection site was a leaf auricle while the big patch was stemmed around the crown tissue. Thus sheath infected large patch was plucked easily than lawn spring dead spot pathogen. This is the first report of an outbreak of the spring dead spot disease on zoysiagrass in the fall season. KCI Citation Count: 0